2021
DOI: 10.3390/app112412079
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Pattern of Oropharyngeal Cancers from North-East Romanian Patients

Abstract: Background: Human papilloma virus (HPV) is acknowledged as a risk factor for oropharyngeal squamous cellular cancers (OPSCC), of which the dominant types are tonsillar (TSCC) and base of tongue cancer (BOTSCC). Objective: To assess the role of HPV in selected OPSCC cases, from Romanian patients by sensitive and complementary molecular assays. Material and Methods: Fifty-four formalin fixed paraffin embedded (FFPE) OPSCC samples were analyzed for HPV DNA by a PCR-based bead-based multiplex-assay. Thirty-four sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…Even so, it is worth mentioning the results published by Ursu et al, who evaluated the HPV status in HNC patients from NE Romania: only 2 HNSCC cases were found to be driven by HPV out of 189 samples. The authors concluded that a very small proportion of HNC can be attributed to the HPV virus, specifically the HPV 16 subtype, which seems to be the most prevalent in our country [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even so, it is worth mentioning the results published by Ursu et al, who evaluated the HPV status in HNC patients from NE Romania: only 2 HNSCC cases were found to be driven by HPV out of 189 samples. The authors concluded that a very small proportion of HNC can be attributed to the HPV virus, specifically the HPV 16 subtype, which seems to be the most prevalent in our country [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our area, NE part of Romania, the external beam radiation therapy (EBRT) with IMRT (intensity modulated radiotherapy) technique is commonly used. Doses are reported in 60 Gy/30 fractions/6 weeks, 70 Gy/35 fractions/7 weeks, or 66 Gy/33 fractions/6.5 weeks, 2 Gy/fraction [16,17].…”
mentioning
confidence: 99%